If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x-2(x+6)=0
We multiply parentheses
5x-2x-12=0
We add all the numbers together, and all the variables
3x-12=0
We move all terms containing x to the left, all other terms to the right
3x=12
x=12/3
x=4
| 7x+5=11+5× | | 8(-1)−6y=16 | | π=-0.2x^2+0.4x+600 | | 7(4w+8)/5=3 | | 5^(x+6)=7 | | 6x+5=-9x2-4 | | 6(x+2)-4(x+3)=7 | | -5(-3z+1)=-45 | | x,2+3x=0 | | -x2=-14 | | 33+x=2x+8 | | 5=36+3x | | 4x-2x,2=5 | | 2(6x+6)=16 | | -1260/84=x | | 11=f+4 | | 3(x=4)=5 | | (7x+3)/2x=3 | | 4*x=-96 | | (5z-4)(2-z)=0 | | 5(3+x)=3x-4 | | .1w^2+2.155w-180=0 | | 2(t=4)=0 | | 2x/3+26=74 | | 8x+33=15x−37 | | 4x-9x=-5x | | 90=9x+4+x+6 | | n+19/7=7 | | 176*(3.2+-0.01818181818y)+y=539 | | 180=14x+4+11x+1 | | 10x+2=19+× | | 85=4x+4+7x-7 |